2006
DOI: 10.1021/bc060002u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Biotin Derivative of Iberiotoxin:  Binding Interactions with Streptavidin and the BK Ca2+-Activated K+ Channel Expressed in a Human Cell Line

Abstract: Iberiotoxin (IbTx) is a scorpion venom peptide that inhibits BK Ca 2+ -activated K + channels with high affinity and specificity. Automated solid phase synthesis was used to prepare a biotin-labeled derivative (IbTx-LC-biotin) of IbTx by substitution of Asp19 of the native 37-residue peptide with N-ε-(d-biotin-6-amidocaproate)-L-lysine. Both IbTx-LC-biotin and its complex with streptavidin (StrAv) block single BK channels from rat skeletal muscle with nanomolar affinity, indicating that the biotin-labeled resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 67 publications
(97 reference statements)
1
25
0
Order By: Relevance
“…Consistent with previous studies (Nimigean and Magleby, 1999;Tricarico et al, 2005;Bingham et al, 2006), this study clearly demonstrated the presence of BK Ca channels in human skeletal muscle cells. Paxilline or iberitoxin was found to block I K(Ca) in these cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (Nimigean and Magleby, 1999;Tricarico et al, 2005;Bingham et al, 2006), this study clearly demonstrated the presence of BK Ca channels in human skeletal muscle cells. Paxilline or iberitoxin was found to block I K(Ca) in these cells.…”
Section: Discussionsupporting
confidence: 92%
“…Paxilline, an indole alkaloid isolated from Penicillium paxilli, has been known as an inhibitor of BK Ca channels . In single-channel recordings, the single-channel conductance of BK Ca channels seen in HSkMCs, was 176 ± 7 pS (n = 9), a value that is similar to that of prototypical BK Ca channels present in skeletal muscle cells (Moczydlowski and Latorre, 1983;Tricarico et al, 2005;Bingham et al, 2006). However, this value is apparently greater than that of small-conductance Ca 2+ -activated K + channels found in differentiated H9c2 myoblast (Wang et al, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…MH + 4265.4 Da, Calc. MH + 4265.8 Da) demonstrated a K d of 1.6 nM via lipid bilayer (Table 1), and demonstrated characteristic discrete long-lived blocked states upon assay by single BK Ca channels as observed in other αKTx1 toxins (see [11,2]; data not shown). Synthetic yields of IbTx-D19C-Acm were ~2% per 100 mg peptide oxidized.…”
Section: Resultsmentioning
confidence: 67%
“…Combining the structure–activity profiles of ChTx [33,34], IbTx [5,8,19], IbTx-chimeras [12], and our previous IbTx derivative studies [2], a suitable thiol-ester ligation construct was designed, containing an orthogonally protected ‘spinster thiol’. Native chemical ligation requires a C-terminal peptide segment (Peptide B) to contain an N-terminal Cys (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation